2019
DOI: 10.1098/rsos.190078
|View full text |Cite
|
Sign up to set email alerts
|

Thermal switch of oscillation frequency in Belousov–Zhabotinsky liquid marbles

Abstract: External control of oscillation dynamics in the Belousov–Zhabotinsky (BZ) reaction is important for many applications including encoding computing schemes. When considering the BZ reaction, there are limited studies dealing with thermal cycling, particularly cooling, for external control. Recently, liquid marbles (LMs) have been demonstrated as a means of confining the BZ reaction in a system containing a solid–liquid interface. BZ LMs were prepared by rolling 50 μl droplets in polyethylene (PE) powder. Oscill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…[23][24][25][26]. Use of liquid marbles for non-traditional computing was reported recently [27][28][29][30]. Liquid marbles may be actuated by UV and IR light and Marangoni flows [31][32][33], and demonstrate obvious potential for micro-fluidics applications [34][35].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26]. Use of liquid marbles for non-traditional computing was reported recently [27][28][29][30]. Liquid marbles may be actuated by UV and IR light and Marangoni flows [31][32][33], and demonstrate obvious potential for micro-fluidics applications [34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of an organic substrate, e.g. malonic acid by bromate ions in acidic medium in the presence of a single-electron transfer metal ion redox catalyst like ferroin, typically known as Belousov-Zhabotinsky reaction [25], has also been reported [26,27] in liquid marbles.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, we proposed to measure oscillations of electrical potential, caused by oxidation wave-fronts by inserting electrodes in the BZ medium-filled LMs. We previously made a prototype BZ marble thermal sensor [2] and demonstrated that it is possible to reduce the frequency of oscillations or even completely halt oscillations by 'freezing' them. This method is robust, but requires Peltier elements and, therefore, lacks the scalability demanded from a computational viewpoint.…”
Section: Introductionmentioning
confidence: 99%